2016
DOI: 10.1002/1873-3468.12421
|View full text |Cite
|
Sign up to set email alerts
|

Linking microbiota and respiratory disease

Abstract: An increasing body of evidence indicates the relevance of microbiota for pulmonary health and disease. Independent investigations recently demonstrated that the lung harbors a resident microbiota. Therefore, it is intriguing that a lung microbiota can shape pulmonary immunity and epithelial barrier functions. Here, we discuss the ways how the composition of the microbial community in the lung may influence pulmonary health and vice versa, factors that determine community composition. Prominent microbiota at ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 167 publications
(203 reference statements)
0
54
0
4
Order By: Relevance
“…The use of BAL fluid and/or bronchoscopial brush specimen is highly invasive and could be also contaminated with pharyngeal or oral microbiota, although it is the most representative specimen of the lung microbiota. 10 Also, mice mod-els used to study TB-microbiome interactions have been suggested to be inefficient. 35 The need for microbiota-Mtb dormancy and persistence interaction research Another important area of research in TB is dormancy and persistence, particularly as most TBexposed or -treated persons develop latent TB, which can be revived into active disease during old age or immunocompromised conditions.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of BAL fluid and/or bronchoscopial brush specimen is highly invasive and could be also contaminated with pharyngeal or oral microbiota, although it is the most representative specimen of the lung microbiota. 10 Also, mice mod-els used to study TB-microbiome interactions have been suggested to be inefficient. 35 The need for microbiota-Mtb dormancy and persistence interaction research Another important area of research in TB is dormancy and persistence, particularly as most TBexposed or -treated persons develop latent TB, which can be revived into active disease during old age or immunocompromised conditions.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…In addition, certain diets (prebiotics), such as lipid-rich ones, can affect or alter the inflammatory profile, that is, can have effects on IL-2, IL-12, and IL-1β, tumor necrosis factor-alpha (TNF-α), and Toll-like receptor (TLR) signaling. 10,18 Can such diets exacerbate or control TB? In addition, findings on the relationship between microbiota and immunity show increasingly significant effects, strengthening the hypothesis that the microbiome may be relevant in treating TB.…”
Section: Introductionmentioning
confidence: 99%
“…It is increasingly appreciated that the gut microbiota also has systemic effects on health, for example through the production of anti-inflammatory metabolites such as short-chain fatty acids (SCFAs) (Tan et al, 2014). In the context of respiratory disease, most studies have focused on how the gut microbiota influences immune responses in the airways (Hauptmann and Schaible, 2016). Changes in gut microbiota composition can change the gut metabolome, with a subsequent impact on host immune function (Corrêa-Oliveira et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of the human microbiome, including the respiratory tract, have demonstrated that the resident microflora is much more abundant and diverse than previously realized; including many species of nonculturable bacteria, viruses [virome], fungi, and protozoa. Present data indicate that the microbiome of the gut and the lungs are linked, by immune cells and mediators, and maybe important and associated with the pathogenesis of respiratory diseases [10][11][12]. The bronchial tract harbors a complex and dynamic microbial milieu of about 500 species, which overlaps with the oral microbiome [10].…”
mentioning
confidence: 83%